Investigation into the Role of PI3K and JAK3 Kinase Inhibitors in Murine Models of Asthma - Wagh, Akshaya D.; Sharma, Manoranjan; Mahapatra, Jogeshwar; Chatterjee, Abhijeet; Jain, Mukul; Addepalli, Veeranjaneyulu (Frontiers in Pharmacology, 2017)
Asthma is a clinical disorder commonly characterized by chronic eosinophilic inflammation, remodeling and hyper responsiveness of the airways. However, the kinases like Phosphoinositide 3 kinase (PI3K) and Janus kinase (JAK3) are involved in mast cell proliferation, activation, recruitment, migration and prolonged survival of inflammatory cells. The present study was designed to evaluate the in-vivo comparative effects of two kinase inhibitors on airway inflammation and airway remodeling in acute and chronic models of asthma. Mice were sensitized twice intra-peritoneally and then challenged by inhalation with ovalbumin (OVA). They developed an extensive inflammatory response, goblet cell hyperplasia, collagen deposition, airway smooth muscle thickening similar to pathologies observed in human asthma. The effects of PI3K inhibitor (30 mg/kg, p.o), JAK3 inhibitor (30 mg/kg, p.o) and Dexamethasone (0.3mg/kg) on airway inflammation and remodeling in OVA sensitized/challenged balb/c mice were evaluated. Twenty-four hours after the final antigen challenge, bronchoalveolar lavage and histological examinations were carried out. It was observed that kinase inhibitors significantly reduced airway inflammation as evidenced by the decrease in pro inflammatory cytokines in BALF and lung homogenate and inflammatory cell count in acute as well as in chronic asthma. Lung histological analysis showed increased infiltration of inflammatory cells, hyperplasia of goblet cells and the collagen deposition, which were significantly reduced with kinase inhibitor. In conclusion, our data suggest that PI3K and JAK3 inhibitors showed promising alternative therapeutic activity in asthma, which might significantly counteract the airway inflammation in patients with allergic asthma.